Advancement in algal bioremediation for organic, inorganic, and emerging pollutants. (15th January 2023) - Dubey, Siddhant; Chen, Chiu-Wen; Haldar, Dibyajyoti; Tambat, Vaibhav Sunil; Kumar, Prashant; Tiwari, Ashutosh; Singhania, Reeta Rani; Dong, Cheng-Di; Patel, Anil Kumar
Abstract: Rapidly changing bioremediation prospects are key drive to develop sustainable options that can offer extra benefits rather than only environmental remediation. Algal remediating is gaining utmost attention due to its mesmerising sustainable features, removing odour and toxicity, co-remediating numerous common and emerging inorganic and organic pollutants from gaseous and aqueous environments, and yielding biomass for a range of valuable products refining. Moreover, it also improves carbon footprint via carbon-capturing offers a better option than any other non-algal process for several high CO2 -emitting industries. Bio-uptake, bioadsorption, photodegradation, and biodegradation are the main mechanisms to remediate a range of common and emerging pollutants by various algae species. Bioadsorption was a dominant remediation mechanism among others implicating surface properties of pollutants and algal cell walls. Photodegradable pollutants were photodegraded by microalgae by adsorbing photons on the surface and intracellularly via stepwise photodissociation and breakdown. Biodegradation involves the transportation of selective pollutants intracellularly, and enzymes help to convert them into simpler non-toxic forms. Robust models are from the green microalgae group and are dominated by Chlorella species. This article compiles the advancements in microalgae-assisted pollutants remediation and value-addition under sustainable biorefinery prospects. Moreover, filling the knowledge gaps, and recommendations for developing an effective platform for emerging pollutants remediation and realization of commercial-scale algal bioremediation. Graphical abstract: Image 1 Highlights: Algal remediation is evolving for emerging organic pollutants from industrial origin. Algal remediation is gaining major focus for persistent organic pollutants removal. Algal remediation offers sustainable solutions and promising circular economy option. It improves environmental-footprint, offsets treatment-costs via valuable products.